Meningkatkan Kemampuan Mengenal Huruf Vokal bagi Anak Slow Learner Melalui Aplikasi Membaca Lancar di Kelas II (Single Subject Research) SD N 03 Batu-Basa - Ikhsan AL Furqan; Arisul Mahdi (Jurnal Penelitian Pendidikan Khusus, 2023)
This study aims to demonstrate that Slow Learner students can effectively improve their ability to read vowel letters using reading learning application media. The research was conducted as an A-B-A design experiment with stubble subjects (Single Subject Research). The percentage score that was collected was the form of the data that was analyzed using graphic and visual analysis. The baseline (A1) results of 16 observations collected over three phases yielded stable data of 0% and flat (=). The data in the intervention phase B were stable at 80% and increased (+). 90% of the stable data came from the baseline phase (A2). The data show that slow learners in class II can effectively improve their ability to read vowel letters with the reading learning application media.